Unsteady coupled heat and mass transfer by mixed convection flow of a micropolar fluid near the stagnation point on a vertical surface in the presence of radiation and chemical reaction. (2015) - Chamkha, Ali J.; EL-Kabeir, S.M.M.; Rashad, A.M.
The effects of radiation and chemical reaction on coupled heat and mass transfer by unsteady mixed convection boundary-layer flow of a micropolar fluid near the region of the stagnation point on a double-infinite vertical flat plate are studied. The free stream velocity and the surface temperature and concentration are assumed to vary linearly with the distance along the surface. The flow is impulsively set into motion and both of the temperature and concentration at the surface are also suddenly changed from that of the ambient fluid. The governing partial differential equations are transformed into a set of non-similar equations and solved numerically by an efficient implicit, iterative, finite-difference method. Various comparisons with previously published work are performed and the results are found to be in excellent agreement. A representative set of numerical results for the velocity, angular velocity, temperature and concentration profiles as well as the skin-friction coefficient, wall couple stress, Nusselt number and the Sherwood number is presented graphically for various parametric conditions and discussed.